CURRENT TRENDS AND DEVELOPMENT OF THE AUTOMOTIVE INDUSTRY IN THE SLOVAK REPUBLIC (Perner's Contacts, 2015)
Automakers often use the services of logistics operators who provide comprehensive solutions for the implementation of transport for the company. These services can be provided only with existence of transport and logistics infrastructure and human capital. The quality of infrastructure and human capital proportionally depends on the quality of services provided. Logistics operator in process of choosing transport mode for export-import transactions take into account transaction costs and total delivery time of delivery.